Asset management in the broadcasting industry at the crossroads of industrial revolution 4.0 - Muhammad Ridzuan Raja Azhar, Raja (International Journal of Psychosocial Rehabilitation, 2020)
Asset management in the broadcasting industry is at the threshold of innovations coping with disruptions at the crossroads of the Industrial Revolution 4.0. Efficient production workflow and content management are critical in the transition to a digital environment. Small and medium-sized broadcasters and vendors are experiencing the brunt as a consequence of technological disruption. Stringent requirements for digitization of content following new quality control (QC) standards in the transition to digitalisation have become imperative. This study explores a scalable media asset management (MAM) solution especially for small-scale content providers. Seeking answers to questions: (1) How would audio-visual archival processes enable transition to the digital workflow? (2) How do SMEs and vendors encounter non-compliance issues. (3) How metadata features would facilitate MAM processes? The study conducted face-to-face in-depth interviews with broadcasters, content providers and vendors, participant observation and content analysis at production operation centers and production houses to understand their operations and issues. A compatible workflow criteria model to be supported by machine learning is proposed at the end of the study.